The Mary Daly Reader - Daly, Mary, 1928-2010 (Book collections on Project MUSE., 2017)
"Utrageous, humorous, inflammatory, Amazonian, intellectual, provocative, controversial, and a discoverer of Feminist word-magic, Mary Daly's influence on Second Wave feminism was enormous. She burst through constraints to articulate new ways of being female and alive. This comprehensive reader offers a vital introduction to the core of Daly's work and the complexities secreted away in the pages of her books. Her major theories Bio-philia, Be-ing as Verb, and the life force within words and major controversies relating to race, transgender identity, and separatism are all covered, and the editors have provided introductions to each selection for context. The text has been crafted to be accessible to a broad readership, without diluting Daly's witty but complicated vocabulary. Begun in collaboration with Daly while she was still alive, and completed after her death in 2010, the chapters in this book will surprise even those who thought they knew her work. They contain highlights from Mary Daly's published works over a forty-year span, including her major books Beyond God the Father, Gyn/Ecology, and Pure Lust, as well as smaller articles and excerpts, with additional contributions from Robin Morgan and Mary E. Hunt. Perfect for those seeking an introduction to this path-breaking feminist thinker, The Mary Daly Reader makes key excerpts from her work accessible to new readers as well as those already familiar with her work who are seeking to access the essence of her thought in a single volume."--Provided by publisher.